The Effectiveness Of Implementing Emerging Warehouse Technologies On Warehouse Operations - Ricardo S. Jimenez; Kim Brian V.David; Ma. Viktoria Monique M. Hawod; Franchezka Nicole L. Calicdan; Pauline Kate M. Coronel (International Journal of Economics and Management Sciences, 2024)
Emerging technologies are transforming warehouse operations, and this study investigated the effectiveness of implementing the Internet of Things (IoT), Radio-Frequency Identification (RFID), Artificial Intelligence (AI), and Robotics into warehouse operations. A descriptive correlational research design was employed, utilizing surveys to gather data from warehouse personnel and focusing on key performance indicators such as inventory accuracy, order fulfillment efficiency, cost reduction, and timely delivery satisfaction. The findings revealed a high level of familiarity with RFID and IoT among warehouse personnel, and a strong belief in the positive impact of these technologies on warehouse operations. However, challenges such as implementation costs, technical issues, and regulatory compliance were identified. Surprisingly, the analysis did not reveal a significant relationship between the implementation of these technologies and their overall effectiveness on warehouse operations. Future research should consider qualitative methodologies and larger sample sizes to explore other factors influencing warehouse performance.